Academy of Clinical Essentials: A Revolutionary Nurse Staffing and Education Model. (January 2023) - Rowen, Lisa; Howett, Maeve; Embert, Casey; Beeson, Nicole; Bosah, Barbara; Chen, Lynn; Day, Jennifer; Nichols, DoRhonja; O'Malley, Cassie
Abstract : A revolutionary academic-practice partnership model was implemented at the University of Maryland Medical System (UMMS) with the University of Maryland School of Nursing, through which the preparation and transition to practice of new graduate nurses were reimagined, resulting in intentional support for staffing the nursing workforce. Groups of nursing students were paired with a UMMS-funded clinical instructor to take a full patient assignment for one 12-hour shift in a UMMS hospital each week. This instructor-led cohort is equivalent to one UMMS nurse and was included in the staffing numbers of participating units.